Herpesvirus-associated central and peripheral nervous system involvement: two clinical cases - T. E. Popova; N. A. Shnayder; M. M. Petrova; T. Ya. Nikolaeva; E. A. Kantimirova; N. V. Isaeva; V. A. Shnayder; Yu. S. Panina; A. V. Dyuzhakova; S. K. Dyuzhakov (Неврология, нейропсихиатрия, психосоматика)
Herpesviruses can directly affect the structure of the nervous system, resulting in encephalitis, and also induce immune-mediated disorders of the peripheral nervous system as sensory-predominant chronic inflammatory demyelinating polyneuropathy (CIDP). Patients with immunodeficiency may simultaneously develop two pathological processes, determining the severity of the condition. Parainfectious limbic encephalitis (PILE) associated with viruses from the family Herpes viridae is a form of chronic herpes encephalitis, which is characterized by dysfunction of the limbic system and by a long-term course with exacerbations. CIDP is a dysimmune disease leasing to peripheral nervous system involvement, which belongs to a class of myelinopathies. The paper describes two clinical cases of a concurrence of chronic PILE and CIDP in middle-aged men who have symptomatic status epilepticus and iatrogenic complications. It characterizes difficulties in diagnosis and the clinical features of chronic herpes infection involving the central and peripheral nervous systems. The given clinical cases suggest that not only neurologistsand epileptologists, but also resuscitation specialists and ngiosurgeons should be particularly alert to the pathology in question.